An antiviral defense role of AGO2 in plants - Harvey, Jagger J.W.; Lewsey, M.G.; Patel, K.; Westwood, J.; Heimsta, S.; Carr, J.P.; Baulcombe, D.C. (Public Library of Science, 2011)
Background: Argonaute (AGO) proteins bind to small-interfering (si)RNAs and micro (mi)RNAs to target RNA silencing against viruses, transgenes and in regulation of mRNAs. Plants encode multiple AGO proteins but, in Arabidopsis, only AGO1 is known to have an antiviral role. Methodology/Principal Findings: To uncover the roles of specific AGOs in limiting virus accumulation we inoculated turnip crinkle virus (TCV) to Arabidopsis plants that were mutant for each of the ten AGO genes. The viral symptoms on most of the plants were the same as on wild type plants although the ago2 mutants were markedly hyper-susceptible to this virus. ago2 plants were also hyper-susceptible to cucumber mosaic virus (CMV), confirming that the antiviral role of AGO2 is not specific to a single virus. For both viruses, this phenotype was associated with transient increase in virus accumulation. In wild type plants the AGO2 protein was induced by TCV and CMV infection. Conclusions/Significance: Based on these results we propose that there are multiple layers to RNA-mediated defense and counter-defense in the interactions between plants and their viruses. AGO1 represents a first layer. With some viruses, including TCV and CMV, this layer is overcome by viral suppressors of silencing that can target AGO1 and a second layer involving AGO2 limits virus accumulation. The second layer is activated when the first layer is suppressed because AGO2 is repressed by AGO1 via miR403. The activation of the second layer is therefore a direct consequence of the loss of the first layer of defense.